2018
DOI: 10.2147/prbm.s167621
|View full text |Cite
|
Sign up to set email alerts
|

Distinct psychopathology of patients who attempted suicide with rodenticide in Taiwan: a comparative study with patients of suicide with paraquat

Abstract: ObjectiveRodenticide as a means of suicide has been documented for centuries. However, this method is often discussed in conjunction with other pesticides. Thus, we aimed to focus on patients who committed suicide with rodenticide and compared them with those who used paraquat for suicide, another frequently used yet lethal method, to highlight the different psychopathology of patients who choose rodenticide as their means of suicide.MethodsA 12-year retrospective chart review was conducted on the medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…We found that patients with previous psychiatric illnesses were more likely present to an ED with intoxication, have more severe intoxication, and die from intoxication. These results are consistent with previous studies that patients with psychiatric illness had higher drug overdose [ 40 43 ]. Additionally, in our study, these patients had longer hospital LOS, but lower daily medical expenses.…”
Section: Discussionsupporting
confidence: 93%
“…We found that patients with previous psychiatric illnesses were more likely present to an ED with intoxication, have more severe intoxication, and die from intoxication. These results are consistent with previous studies that patients with psychiatric illness had higher drug overdose [ 40 43 ]. Additionally, in our study, these patients had longer hospital LOS, but lower daily medical expenses.…”
Section: Discussionsupporting
confidence: 93%
“…We found that patients with previous psychiatric illnesses were more likely present to an ED with intoxication, have more severe intoxication, and die from intoxication. These results are consistent with previous studies that patients with psychiatric illness had higher risks of drug overdose (30)(31)(32)(33). However, in our study these patients had longer hospital LOS, but lower daily medical expenses.…”
Section: Discussionsupporting
confidence: 93%
“…Eighteen of the twenty studies (90%) showed a higher proportion of females than males in suicidal populations, with five studies having women representing more than 80% of the sample: 86% female in Magat et al’s study, 83% in Zhargami et al, 81.5% in Suss et al, 80.4% in Farzeneh et al and 80% in Abumadani et al [12,13,14,20,21]. The two studies with a majority of male participants were both from Taiwan: with 60% male participants in Lin’s 2012 study of charcoal poisoning, and 75% male in Lin’s 2018 study of rodenticide and paraquat poisoning (78% in the paraquat subgroup were male) [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…A number of the studies reviewed found AD to be a common diagnosis among those presenting for emergency assessment following self-harm. The lowest proportion of AD found was reported by Lin et al (9.8%) in patients presenting with self-poisoning with either rodenticide or paraquat in Taiwan [27]. Ghimire et al reported that 13.5% of the patients presenting to a Nepalese ED with self-poisoning had a clinical diagnosis of AD [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation